Flexible sensor with built-in directional coil spring skeleton and method of making same
Patent Information
- Application Number
- CN202611122863.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-28
AI Technical Summary
[0012]本发明的目的是提供一种具有内置定向螺旋弹簧骨架的柔性传感器及其制备方法,通过嵌入高模量高分子定向螺旋弹簧作为结构骨架,利用“高模量弹簧强制恢复”机制从根本上解决基体疲劳失效问题,显著提升传感器的循环寿命,同时实现传感器性能的独立可设计性
(1)通过“高模量弹簧强制恢复”机制,从根本上解决柔性传感器基体的疲劳失效问题,显著提升循环寿命。本发明将弹性模量远高于基体的高分子定向螺旋弹簧嵌入基体内部,在外部载荷作用下弹簧承担主要应力发生弹性变形;卸载后弹簧储存的弹性势能释放,强制低模量基体快速、完全恢复至原始形状。该机制不依赖基体材料自身的回弹性,从根本上抑制了基体的塑性变形累积和疲劳裂纹扩展。同时,该设计将“回弹性”功能转移给内置弹簧,基体只需满足低模量要求,从而允许使用极软材料,拓宽了材料选择范围。
Smart Images

Figure CN122631248B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible sensors, and in particular to a flexible sensor with a built-in directional helical spring skeleton and its fabrication method. Background Technology
[0002] Flexible sensors can convert mechanical stimuli (such as pressure and strain) into electrical signals. Due to their good flexibility, extensibility and adhesion, they have broad application prospects in wearable health monitoring, human-computer interaction, intelligent robots and artificial intelligence.
[0003] Currently, most mainstream flexible sensors use flexible polymer elastomers such as polydimethylsiloxane (PDMS), thermoplastic polyurethane (TPU), and hydrogel as matrix materials. By constructing conductive networks (such as metal nanoparticles, carbon nanotubes, graphene, etc.) on or inside the matrix, they can sense mechanical signals such as external pressure and strain.
[0004] However, existing flexible sensors generally suffer from insufficient durability in practical applications. Under repeated cyclic loading such as pressing, bending, and stretching, flexible matrix materials are prone to irreversible plastic deformation and fatigue damage, leading to decreased sensor sensitivity, baseline drift, and ultimately failure. This problem is particularly prominent in applications requiring long-term stable monitoring, such as electronic skin and intelligent prosthetics. The reasons for this are that existing flexible materials have inherent limits in their resilience and fatigue resistance, and traditional sensor structures lack effective internal stress dissipation and deformation recovery mechanisms. Especially when sensors use extremely soft matrices, such as low-crosslinked hydrogels or ultra-soft silicone, to achieve high sensitivity, the problem of plastic deformation of the matrix becomes more severe, often resulting in significant performance degradation after only a few hundred cycles.
[0005] To address the aforementioned problems, existing technologies primarily focus on the following areas: One approach is material modification. This involves enhancing the fatigue resistance of the matrix by adding nanofillers (such as silica and carbon nanotubes), increasing crosslinking density, or developing novel elastomers (such as dual-network hydrogels and self-healing polyurethanes). However, these methods often sacrifice sensor flexibility or sensitivity while improving durability, and the fatigue threshold of the material itself still has an upper limit, making it difficult to meet the requirements of long-term cyclic loading.
[0006] The second direction is microstructure design. This involves constructing micro-pyramids, micro-pillars, micro-wrinkles, and other geometric structures within the dielectric or sensing layer to enhance sensitivity or achieve anisotropic response. However, these microstructures primarily optimize sensing performance and have limited effectiveness in suppressing plastic deformation of the substrate under cyclic loading. Furthermore, the microstructures themselves are prone to irreversible damage after repeated compression.
[0007] Thirdly, there is the direction of the built-in conductive spring body. Chinese invention patent CN107287685A, published on October 24, 2017, discloses an elastic sensor and a method for preparing the elastic composite therein. This scheme adds a carbon spring body (carbon filaments or carbon fibers wound around a central axis at a certain pitch to form a spring shape) to a polyurethane matrix, utilizing the electrical properties of the carbon spring body to achieve sensing. However, in this scheme, the carbon spring body is uniformly dispersed in the matrix as a conductive filler, its function being to construct a conductive network rather than structural reinforcement; the elastic modulus matching design between the carbon spring body and the matrix is not involved, failing to fundamentally solve the problem of accumulated plastic deformation and fatigue failure of the matrix itself.
[0008] Fourthly, there is the area of elastic transfer methods. Chinese invention patent CN116330688A, published on June 27, 2023, proposes an elastic transfer method, preparation method, and application for helical structural materials. This method first winds fibers onto an elastomer to form a helical structural material, then places the helical structural material in a mold and fills it with a matrix material. After the matrix solidifies, the elastomer is pulled out and demolded, forming a hollow helical structural material. In this method, the helical structure only serves as a temporary template, and the final product is a hollow structure. The helical fibers themselves are not retained as a functional skeleton in the final product, and therefore cannot perform the structural function of forcing the matrix to recover its deformation. Furthermore, the helical structure prepared by this method is fiber-wound, making it difficult to precisely control the geometric parameters of the helix (wire diameter, pitch, mean diameter, etc.).
[0009] In addition, existing methods for fabricating flexible sensors mostly employ spinning or molding, which makes it difficult to achieve precise orientation and array distribution of polymer microsprings. Sensor performance parameters (such as sensitivity, range, and linearity) are highly coupled, and changing a certain parameter often requires redesigning the entire sensor structure, making independent adjustment difficult and resulting in low efficiency in customized development for different application scenarios.
[0010] In summary, the problem of substrate fatigue failure under cyclic loading in existing flexible sensors has not been effectively solved. At the same time, the built-in springs in the existing technology are all made of carbon or fiber materials, and their function is positioned as conductive fillers or temporary templates. There is no technical solution to embed high-modulus polymer helical springs as permanent structural skeletons into the substrate to force the substrate to recover its deformation. The coupling problem of sensor performance parameters has also not been effectively solved.
[0011] Therefore, how to significantly improve the fatigue resistance and cycle life of sensors while maintaining substrate flexibility and sensing sensitivity, and how to achieve independent designability of sensor performance, are technical challenges that urgently need to be solved in this field. Summary of the Invention
[0012] The purpose of this invention is to provide a flexible sensor with a built-in directional helical spring skeleton and its preparation method. By embedding a high-modulus polymer directional helical spring as a structural skeleton, the fatigue failure problem of the matrix is fundamentally solved by utilizing the "high-modulus spring forced recovery" mechanism, which significantly improves the cycle life of the sensor and realizes the independent designability of the sensor performance.
[0013] To achieve the above objectives, the present invention provides a flexible sensor with a built-in directional helical spring skeleton, comprising a flexible polymer matrix, at least one polymer directional helical spring embedded in the flexible polymer matrix, a conductive layer disposed on the upper surface of the flexible polymer matrix, and electrodes disposed at both ends of the conductive layer. The elastic modulus of the polymer-oriented helical spring is higher than that of the flexible polymer matrix, and the ratio of the elastic modulus of the polymer-oriented helical spring to that of the flexible polymer matrix is... 10:1; Polymer oriented helical springs are used to bear the main stress and undergo elastic deformation under external loads, and to force the flexible polymer matrix to return to its original shape through the stored elastic potential energy after the load is unloaded.
[0014] Preferably, the polymer-oriented helical spring is made of a high-modulus polymer elastomer with a cured elastic modulus of 5~500MPa and a Shore hardness of 50A~80D; the flexible polymer matrix is made of a low-modulus polymer elastomer with a cured elastic modulus of 2~20MPa and a Shore hardness of 50A~80A.
[0015] Preferably, the number of polymer oriented helical springs is 1 to 100, arranged in a rectangular array, hexagonal array or ring array inside the flexible polymer matrix, and the center distance between adjacent springs is 5 to 20 mm; The conductive layer is a flexible conductive carbon paste layer with a thickness of 5~30μm, which is formed on the upper surface of a flexible polymer matrix by a scraping process; the electrode is a flexible copper wire, which is fixed to both ends of the conductive layer by conductive silver paste.
[0016] Preferably, it also includes an encapsulation layer, which covers the surface of the conductive layer and has a thickness of 20~100μm. The material is the same as that of the flexible polymer matrix.
[0017] This invention also provides a method for fabricating a flexible sensor with a built-in directional helical spring skeleton, comprising the following steps: Step 1: Prepare a stacked mold with a spirally connected cavity: Take several thin plates and process through holes in the central area of each thin plate; stack the processed thin plates in sequence, with the center of the through holes of adjacent thin plates having a horizontal offset in the plate plane, and the adjacent thin plates rotating relative to each other around a central axis perpendicular to the plate plane by a certain angle; fix the stacked multi-layer thin plates into an integral mold, with the through holes at the top and bottom of the integral mold serving as the injection end and overflow end, respectively; Step 2, Vacuum-assisted injection molding of polymer oriented helical springs: Place the integral mold obtained in Step 1 in a vacuum environment, inject liquid high-modulus polymer elastomer precursor into the spiral cavity of the integral mold through the through hole at the injection end, and demold after solidification to obtain an independent polymer oriented helical spring. Step 3, Combining the spring with the flexible matrix: Place at least one polymer oriented helical spring obtained in Step 2 into a matrix mold; pour uncured low-modulus polymer elastomer precursor into the matrix mold to completely submerge the polymer oriented helical spring; after curing, demold to obtain a flexible matrix composite material with a polymer oriented helical spring skeleton embedded inside. Step 4, Surface conductive functionalization: A conductive layer is formed on the upper surface of the composite material obtained in step 3, and electrodes are formed at both ends of the conductive layer; Among them, the elastic modulus of the polymer-oriented helical spring is higher than that of the flexible polymer matrix, and the ratio of the elastic modulus of the polymer-oriented helical spring to that of the flexible polymer matrix is ≥10:1.
[0018] Preferably, in step 1, the thin plate is a polymethyl methacrylate thin plate, the quantity is 10 to 50 pieces, the thickness of each thin plate is 0.1 to 0.5 mm, and the planar dimensions are 5 to 20 cm in length and 5 to 20 cm in width; the through hole is an elliptical through hole with a major axis of 1.0 to 3.0 mm and a minor axis of 0.5 to 1.5 mm; the horizontal offset of the center of the elliptical through hole of two adjacent thin plates in the plate plane is 0.1 to 1.0 mm, and the two adjacent thin plates are rotated relative to each other about a central axis perpendicular to the plate surface by 15° to 45°; Adjacent thin plates are bonded and fixed together with UV-curable adhesive. During bonding, several adhesive dots are applied to the edge area between each two layers of thin plates. Each adhesive dot has a diameter of 1~2mm and the distance between adjacent adhesive dots is 5~10mm. A pressure of 0.1~0.3MPa is applied and the plates are cured by UV light irradiation for 10~30 seconds.
[0019] Preferably, in step 2, the absolute pressure of the vacuum environment is 100~1000Pa; the injection adopts a vacuum-assisted injection method, injecting the liquid high-modulus polymer elastomer precursor from the through hole at the injection end until liquid flows out from the through hole at the overflow end, then stop evacuating the vacuum and keep the vacuum standing for 5~15 minutes; demolding adopts a mechanical peeling method to peel off all the thin plates layer by layer. In step 2, the high-modulus polymer elastomer is thermosetting polyurethane, silicone rubber, or polyurea elastomer, with an elastic modulus of 5~500MPa after curing. The curing conditions are: thermosetting polyurethane is cured at 80~120℃ for 1~4h, and silicone rubber is cured at room temperature for 24h or at 80℃ for 1h.
[0020] Preferably, in step 3, the number of polymer oriented helical springs is 1 to 100, which are placed in an array layout in the matrix mold. The array layout is a rectangular array, a hexagonal array, or a ring array, and the center distance between adjacent springs is 5 to 20 mm. Before placing the spring, first coat the bottom of the base mold with an uncured low-modulus polymer elastomer precursor, and then gently press the spring to fix it. After casting, place the mold in a vacuum environment with an absolute pressure of 500~1500Pa for 20~60 minutes to remove air bubbles, and then cure it according to the curing conditions of the base material. The low-modulus polymer elastomer is thermoplastic polyurethane, silicone rubber or thermosetting polyurethane, with an elastic modulus of 2~20MPa after curing. The curing conditions are as follows: thermoplastic polyurethane is cooled and shaped, silicone rubber is cured at room temperature to 80℃ for 1~24h, and thermosetting polyurethane is cured at 80~120℃ for 1~4h.
[0021] Preferably, the conductive layer in step 4 includes: wiping the surface of the composite material obtained in step 3 clean with anhydrous ethanol; treating its upper surface with oxygen plasma at a power of 50-100W, a pressure of 20-50Pa, and a treatment time of 30-120s; uniformly coating the surface with conductive paste using a scraping process, resulting in a wet film thickness of 30-80μm; curing at 80-120℃ for 30-90min to obtain a conductive layer with a thickness of 5-30μm; applying conductive silver paste to both ends of the conductive layer and pressing it with flexible copper wires, then curing at room temperature for 30-60min.
[0022] Preferably, the process further includes an encapsulation step: coating a non-conductive flexible protective layer with a thickness of 20~100μm onto the surface of the conductive layer where the electrodes have been led out, using the same material as the low-modulus polymer elastomer; setting a mask or reserving an opening at the electrode lead-out position before coating; and curing according to the curing conditions of the substrate material after coating.
[0023] Therefore, the flexible sensor with a built-in directional helical spring skeleton and its preparation method of the present invention have the following beneficial effects: (1) By using the "high-modulus spring forced recovery" mechanism, the fatigue failure problem of the flexible sensor substrate is fundamentally solved, and the cycle life is significantly improved. This invention embeds a polymer-oriented helical spring with an elastic modulus much higher than that of the substrate into the substrate. Under external load, the spring bears the main stress and undergoes elastic deformation. After unloading, the elastic potential energy stored in the spring is released, forcing the low-modulus substrate to quickly and completely recover to its original shape. This mechanism does not rely on the resilience of the substrate material itself, fundamentally inhibiting the accumulation of plastic deformation and fatigue crack propagation of the substrate. At the same time, this design transfers the "resilience" function to the built-in spring, and the substrate only needs to meet the low modulus requirement, thereby allowing the use of extremely soft materials and broadening the range of material selection.
[0024] (2) The "layered rotational misalignment mold + vacuum infusion + mechanical peeling" preparation method achieves low-cost, high-precision, and scalable manufacturing of polymer microsprings, and the process is environmentally friendly and safe. This invention involves stacking laser-drilled PMMA thin plates layer by layer, forming a spiral interconnected cavity mold through horizontal misalignment and layer-by-layer rotation; vacuum infusion is used to completely fill the complex cavity with polymer elastomer; after curing, the thin plates are peeled off layer by layer by mechanical peeling to obtain independent polymer oriented helical springs. This method is low-cost, has controllable precision, uses universal materials, requires no organic solvents, is environmentally friendly and safe, and is suitable for mass production.
[0025] (3) Sensor performance can be designed independently. The conductive functionalization process is simple, safe, and firmly bonded, and the overall technical solution has high practicality and scalability. The mechanical response of this invention is contributed by two independent parts: the strain response of the surface conductive layer (determining sensitivity) and the compressive stiffness of the spring skeleton (determining range and linearity). By adjusting the geometric parameters of the spring (wire diameter, pitch, number, array density), the sensor range can be changed independently without changing the substrate material and conductive layer; conversely, by changing the substrate with different moduli or adjusting the conductive layer formula, the sensitivity can be adjusted without changing the spring structure. This decoupled design greatly simplifies the customized development of sensors for different application scenarios. At the same time, the conductive functionalization adopts oxygen plasma pretreatment, commercial flexible conductive carbon paste coating, and thermosetting, which does not require hazardous chemicals such as ammonia and formaldehyde, and is suitable for various substrate materials such as TPU, silicone, and polyurethane. The conductive layer is firmly bonded to the substrate and does not peel off after thousands of cycles of pressing.
[0026] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the manufacturing process of the flexible sensor with a built-in polymer oriented helical spring skeleton of the present invention. Figure 2This is a schematic diagram of the structure of a single thin plate of the flexible sensor with a built-in polymer oriented helical spring skeleton of the present invention. Figure 3 This is a scanning electron microscope image of the polymer oriented helical spring inside the sensor in Embodiment 1 of the present invention; Figure 4 This is a schematic diagram of the compressive deformation of the sensor obtained in Example 1 under normal pressure; Figure 5 This is a graph showing the pressure-resistance response of the sensor obtained in Embodiment 1 of the present invention under different pressure ranges; Figure 6 This is a graph showing the resistance response monitoring results of the sensor obtained in Embodiment 2 of the present invention under 5000 consecutive compressive deformations; Figure 7 This is a graph showing the change in the peak resistance rate of the sensor obtained in Comparative Example 1 of the present invention as a function of the number of cycles under cyclic loading. Figure 8 This is a graph showing the change in the peak resistance rate of the sensor obtained in Comparative Example 2 of the present invention as a function of the number of cycles under cyclic loading. Detailed Implementation
[0028] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0030] The "polymer oriented helical spring" involved in this invention refers to a polymer elastomer structure with a precise three-dimensional helical geometry, where multiple springs are arranged in a consistent orientation within a flexible matrix, prepared by a stacked, rotating, and misaligned mold. This structure differs from the randomly oriented or biomimetic helical fibers in the prior art; its helical axis direction is controllable through mold design, and it is used to force the matrix to recover its deformation after the external load is unloaded.
[0031] The following section further describes the fabrication process of a flexible sensor with a built-in polymer oriented helical spring skeleton. It should be noted that the specific parameters involved in the following steps (such as plate thickness, aperture size, offset, rotation angle, vacuum level, temperature, time, etc.) are all exemplary ranges, and those skilled in the art can make appropriate adjustments within these ranges based on actual materials and equipment conditions.
[0032] like Figure 1 As shown, it includes the following steps: Step 1: Prepare a stacked mold with a spirally connected cavity: Select polymethyl methacrylate (PMMA) sheets with a thickness of 0.1~0.5mm as the mold base material, with a planar dimension of 5~20cm in length and 5~20cm in width. The number of sheets is 10~50.
[0033] Using laser marking equipment, a through-hole in an elliptical shape is machined in the center area of each thin plate, such as... Figure 2 As shown, L, W, and h represent the length, width, and thickness of the thin plate, respectively, and a and b represent the major and minor axes of the elliptical through-holes in each thin plate, respectively. The major axis of the through-hole is 1.0~3.0mm, and the minor axis is 0.5~1.5mm. The power and speed of laser marking are adjusted according to the thickness of the thin plate to ensure that the edges of the through-holes are smooth and burr-free. The size of the through-hole determines the wire diameter of the final spring.
[0034] The processed thin plates are stacked sequentially. The following two conditions must be met during stacking: (1) Horizontal misalignment: The horizontal offset of the center of the elliptical through hole of two adjacent thin plates in the plate plane is 0.1~1.0mm. This offset causes the holes of the upper and lower layers to overlap, forming a connected channel. If the offset is too small, the channel will be narrow, which is not conducive to subsequent slurry filling; if the offset is too large, the cross-sectional area of the channel will be too small or it will be broken.
[0035] (2) Layer-by-layer rotation: The two adjacent thin plates are rotated relative to each other by 15°~45° around the central axis perpendicular to the plate surface. As the number of layers accumulates, the three-dimensional cavity formed by the overlapping of the elliptical holes in each layer presents as a continuous spiral rising (or falling) tubular cavity. The rotation angle determines the pitch of the spring: the larger the angle, the larger the pitch; the smaller the angle, the smaller the pitch.
[0036] The stacked multilayer thin plates are bonded together with ultraviolet light curing adhesive (UV adhesive) and local solvent bonding with solvents such as acetone to fix them into an integral mold. The through holes at the top and bottom of the integral mold serve as the filling end and overflow end, respectively.
[0037] The following embodiments use UV adhesive bonding as an example for further explanation. During bonding, several UV adhesive bonding dots are applied (rather than full coating) to the edge area between every two thin plates. Each bonding dot is approximately 1-2 mm in diameter, and the distance between adjacent bonding dots is approximately 5-10 mm. After alignment, a pressure of 0.1-0.3 MPa is applied, and the mixture is irradiated with a UV light source for 10-30 seconds to allow the adhesive layer to fully cure. This dot application method ensures that there is no relative movement between the thin plates and no leakage during subsequent vacuum infusion, while also facilitating mechanical peeling layer by layer after curing. The through holes at the top and bottom of the mold are connected to the internal spiral cavity.
[0038] Step 2: Vacuum-assisted injection molding of polymer springs: The spring material is a high-modulus polymer elastomer. The cured high-modulus polymer elastomer has an elastic modulus of 5~500 MPa and a Shore hardness of 50A~80D. The materials used in the following examples include: high-hardness thermosetting polyurethane, high-hardness silicone rubber, and high-hardness polyurea elastomer.
[0039] Place the integral mold obtained in step 1 into a vacuum casting equipment, evacuate to an absolute pressure of 100~1000Pa, and maintain this vacuum level for 2~5 minutes to fully expel the air from the spiral cavity inside the mold.
[0040] Slowly inject the liquid spring precursor (pre-degassed in a vacuum container for 10-30 minutes) through the through-hole at the filling end. Keep the vacuum pump running continuously to continuously evacuate the gas from the cavity. When continuous liquid flow is observed from the through-hole at the overflow end, stop the injection and vacuuming. Maintain the vacuum for 5-15 minutes to ensure the cavity is completely filled and free of air bubbles.
[0041] Turn off the vacuum pump and remove the mold from the vacuum casting equipment. Curing should then proceed according to the curing conditions selected for the spring material. If thermosetting polyurethane materials are selected, place the mold in an oven at 80~120℃ and cure for 1~4 hours; If silicone materials are used, the mold should be cured at room temperature (20~25℃) for 24 hours, or in an 80℃ oven for 1 hour. If polyurea elastomer is selected, it should be cured at room temperature or under heating conditions according to the material instructions.
[0042] After curing, demolding is performed using a mechanical peeling method: Tweezers are used to grasp the edge of the outermost PMMA sheet, and a blade is used to gently pry it up, peeling off all PMMA sheets layer by layer along the UV adhesive bonding points. Because the UV adhesive is only applied in dots, the bonding area is small, and the adhesive layer is easily broken during peeling, without damaging the spring structure. After peeling, an independent polymer-oriented helical spring is obtained. If a small amount of UV adhesive remains, it can be gently wiped away with a soft brush or anhydrous ethanol.
[0043] In this step, the spring material can also be high-hardness thermoplastic polyurethane (TPU), which is melted, poured in, and then cooled to form the spring.
[0044] Step 3: Modulus matching and composite bonding of spring and flexible substrate: The matrix material is a low-modulus polymer elastomer. The cured low-modulus polymer elastomer has an elastic modulus of 2-20 MPa and a Shore hardness of 50A-80A (A scale). The materials used in the following examples include: low-hardness thermoplastic polyurethane (TPU), low-hardness silicone rubber, and low-hardness polyolefin elastomer. The elastic modulus ratio of the spring material to the matrix material must be ≥10:1. This ratio is the lower limit to ensure the effective functioning of the spring's forced return function: if the ratio is lower than 10:1, the elastic energy stored in the spring is insufficient to overcome the plastic deformation of the matrix, and the durability improvement effect is not significant. The upper limit of the modulus ratio is not specifically limited; in practical applications, it can be selected based on the fracture toughness of the matrix material, generally not exceeding 100:1, to avoid localized stress concentration at the spring ends that could damage the matrix. Those skilled in the art can determine the appropriate modulus ratio for a specific material combination through conventional experiments.
[0045] One or more polymer-oriented helical springs obtained in step 2 are placed in a mold according to the designed array layout. The mold can be customized according to the required sensor shape, such as cylindrical, square, or rectangular. The number of springs is 1 to 100, and the center distance between adjacent springs is 5 to 20 mm.
[0046] To prevent the spring from moving or floating during the pouring process, a small amount of uncured base material is pre-coated on the bottom of the mold, and the spring is gently pressed and fixed. After it has partially cured (or cooled and solidified), the subsequent pouring can be carried out.
[0047] The uncured matrix precursor is poured into the mold, completely submerging all the springs. The shape of the matrix precursor depends on the selected material: If thermoplastic polyurethane (TPU) is selected, the TPU particles are heated to 180~220℃ to melt, and a molten precursor is obtained. If liquid silicone prepolymer is selected, it can be used directly after being mixed in the correct proportion. If thermosetting polyurethane is selected, the two-component prepolymer should be mixed before use.
[0048] Place the mold containing the spring and the matrix precursor in a vacuum drying oven, evacuate to an absolute pressure of 500~1500Pa, and maintain for 20~60 minutes to remove air bubbles. Then cure according to the curing conditions of the matrix material: TPU: Cool the mold to room temperature to allow the TPU to solidify and set. Organosilicon: Curing at room temperature to 80°C for 1 to 24 hours; Thermosetting polyurethane: Cured at 80~120℃ for 1~4 hours.
[0049] After curing, the composite material is removed from the mold. The resulting composite material has an embedded helical spring skeleton inside and a flexible matrix on the outside.
[0050] In this step, the matrix material can also be hydrogel or polyolefin elastomer, and the curing conditions should be adjusted accordingly.
[0051] Step 4: Surface conductive functionalization: Wipe the surface of the composite material obtained in step 3 with anhydrous ethanol to remove oil and impurities, and let it air dry naturally.
[0052] The upper surface of the composite material is treated with oxygen plasma to increase its surface energy and enhance the adhesion of the subsequent conductive layer. Plasma treatment parameters: power 50~100W, pressure 20~50Pa, treatment time 30~120s. For substrate materials with high surface energy (such as TPU), this step can be omitted; for materials with low surface energy (such as silicone), plasma treatment or a primer treatment is necessary.
[0053] A commercial flexible conductive carbon paste was uniformly coated onto the upper surface of the composite material using a blade coating process, with a wet film thickness of 30–80 μm. During the blade coating process, a blade or coating rod was used, maintaining a uniform speed and pressure.
[0054] The coated composite material is placed in an oven and cured at 80-120℃ for 30-90 minutes to obtain a conductive layer with a thickness of 5-30 μm. The curing temperature and time are adjusted according to the product instructions of the conductive paste to ensure that the conductive layer is fully cured and firmly bonded to the substrate.
[0055] Conductive silver paste is applied to both ends of the conductive layer (at the electrode positions determined by the sensor design), and flexible copper wires are then crimped together. The mixture is left at room temperature for 30–60 minutes to allow the conductive silver paste to cure and form a stable electrical connection.
[0056] In this step, the conductive layer can be coated by screen printing, using a 100-300 mesh screen, and the paste is squeezed through the screen and transferred to the substrate surface by a squeegee; conductive silver paste can also be used as the conductive paste.
[0057] Step 5, Packaging: A non-conductive flexible protective layer is then coated onto the surface of the conductive layer after the electrodes have been led out to prevent the conductive layer from being worn or oxidized during use. The protective layer material is the same as the substrate material. The coating method is blade coating. Spray coating or spin coating can also be used as alternatives.
[0058] Before coating, a mask or a pre-reserved opening is set at the electrode lead-out position to ensure that the electrode is not covered by the protective layer.
[0059] After coating, cure according to the curing conditions of the protective layer material (refer to step 3).
[0060] Through the above steps, a flexible sensor with a built-in helical spring skeleton is obtained. Under external load, the internal high-modulus spring bears the main stress and forces the substrate to return to its original shape after unloading, thereby significantly improving the sensor's fatigue resistance and cycle life.
[0061] Example 1 This embodiment provides a flexible sensor with a built-in polymer oriented helical spring skeleton, using a thermosetting polyurethane spring and a thermoplastic polyurethane matrix. The specific preparation steps are as follows.
[0062] Step 1: Prepare a stacked mold with a spirally connected cavity: Forty polymethyl methacrylate (PMMA) sheets, each 0.1 mm thick and 10 cm long and 10 cm wide, were used. Elliptical through-holes with a major axis of 2.0 mm and a minor axis of 1.0 mm were laser-marked in the center of each sheet. The sheets were then stacked sequentially, with the center of the elliptical through-holes between adjacent layers offset horizontally by 0.3 mm, and the layers rotated 40° relative to each other. UV adhesive was applied to the edge areas between each pair of sheets (1 mm in diameter, 8 mm apart), and a pressure of 0.2 MPa was applied. The layers were then cured by UV light for 15 seconds. The through-holes at the top and bottom of the stacked sheets served as the injection and overflow ends, respectively. This created a continuous spiraling tubular cavity inside the mold.
[0063] Step 2: Vacuum-assisted injection molding of polymer directional helical springs: The spring material is a thermosetting polyurethane prepolymer (Smooth-Cast65D), with a cured elastic modulus of 250 MPa and a Shore hardness of 65D. The mold is placed in a vacuum casting apparatus, and a vacuum is drawn to an absolute pressure of 500 Pa. Liquid prepolymer (pre-degassed for 20 minutes) is injected through the through-hole at the injection end until liquid flows out from the through-hole at the overflow end, and the vacuum is maintained for 10 minutes. The mold is then removed and placed in a 100℃ oven for curing for 2 hours. After curing, all PMMA sheets are peeled off layer by layer using a mechanical peeling method to obtain an independent polymer-oriented helical spring. Figure 3 As shown, scanning electron microscopy reveals that the spring has a uniform three-dimensional helical structure, with a wire diameter of approximately 0.3 mm, a pitch of approximately 0.6 mm, and an outer diameter of approximately 2.8 mm.
[0064] Step 3: Modulus matching and composite bonding of spring and flexible substrate: The matrix material used is thermoplastic polyurethane (TPU, hardness 60A), with an elastic modulus of 8 MPa and a spring-to-matrix modulus ratio of approximately 31:1. Nine polymer-oriented helical springs obtained in step 2 were placed in a 3×3 rectangular array within a square mold (30 mm side length, 5 mm height), with a center-to-center distance of 12 mm between adjacent springs. A small amount of uncured TPU melt was pre-coated to the bottom of the mold, and the springs were gently pressed in place. TPU granules were heated to 200°C to melt and poured into the mold, completely submerging all the springs. The mold was placed in a vacuum drying oven, and a vacuum was drawn to an absolute pressure of 1000 Pa, maintained for 30 minutes to remove air bubbles. The mold was then cooled to room temperature to allow the TPU to solidify and solidify. After demolding, a flexible matrix composite material with nine springs embedded inside was obtained.
[0065] Step 4: Surface conductive functionalization: The surface of the composite material was wiped clean with anhydrous ethanol. The upper surface was then treated with oxygen plasma at a power of 80W, a pressure of 30Pa, and a treatment time of 60s. A commercial flexible conductive carbon paste (DuPont 7102) was uniformly coated onto the upper surface using a blade coating process, resulting in a wet film thickness of 50μm. The film was cured at 100℃ for 60min to obtain a conductive layer approximately 15μm thick. Conductive silver paste was then applied to both ends of the conductive layer, and flexible copper wires were crimped onto them. The layer was then allowed to cure at room temperature for 45min.
[0066] Step 5, Packaging: On the conductive layer surface where the electrodes have been led out, a non-conductive TPU protective layer with a thickness of 50 μm is coated using a scraping process. Before coating, openings are made at the electrode locations. After coating, the layer is cured at 80°C for 30 minutes to obtain the flexible sensor.
[0067] The performance of the obtained flexible sensor was tested: 1) Normal stress test: such as Figure 4 As shown, when the normal pressure is applied perpendicularly to the upper surface of the sensor, the internal spring undergoes compression deformation, and the surface conductive layer undergoes tensile strain along with the substrate, causing the conductive path in the conductive carbon paste layer to be partially broken, resulting in an increase in resistance.
[0068] 2) Use a universal testing machine in conjunction with a resistance tester for testing. Figure 5 The resistance-pressure response curves of the sensor are shown in the range of 0–200 kPa. In the low-pressure region of 0–50 kPa, the rate of change of resistance (…) R / R0 increases approximately linearly with increasing pressure, with a sensitivity of approximately 0.004 kPa. -1 At 50 kPa, the rate of change of resistance reaches about 20%; in the range of 50~150 kPa, the slope of the curve gradually decreases, and the rate of change of resistance increases from 20% to about 35%; above 150 kPa, it enters the compression plateau region, and the rate of change of resistance tends to saturate, with a maximum value of about 38%.
[0069] Example 2 This embodiment provides another flexible sensor with a built-in polymer oriented helical spring skeleton, which uses an organosilicon spring and an organosilicon substrate. The specific preparation steps are as follows.
[0070] Step 1: Prepare a stacked mold with a spirally connected cavity: Thirty PMMA sheets with a thickness of 0.3mm were selected, each with a planar dimension of 15cm in length and 15cm in width. Elliptical through-holes were machined using laser marking equipment, with a major axis of 2.5mm and a minor axis of 1.2mm. During stacking, adjacent layers were horizontally offset by 0.5mm and rotated 25° relative to each other. UV adhesive dispensing parameters were: bonding point diameter 1.5mm, spacing 10mm, pressure 0.25MPa, and curing under UV irradiation for 20 seconds. The through-holes at the top and bottom of the stacked sheets served as the injection and overflow ends, respectively, connecting to the internal spiral cavity.
[0071] Step 2: Vacuum-assisted injection molding of polymer directional helical springs: The spring material is addition-cured silicone rubber (Smooth-Sil950), with an elastic modulus of approximately 8 MPa and a Shore hardness of 50A after curing. The mold is evacuated to an absolute pressure of 300 Pa. Liquid silicone prepolymer (pre-degassed for 15 minutes) is injected through the injection port. Under vacuum, it is drawn in and fills the cavity until liquid flows out of the overflow port. Vacuuming is then stopped, and the vacuum is maintained for 12 minutes. After curing at room temperature for 24 hours, the spring is mechanically peeled off and demolded to obtain a silicone helical spring with a wire diameter of approximately 1.2 mm and a pitch of approximately 0.9 mm.
[0072] Step 3: Modulus matching and composite bonding of spring and flexible substrate: The matrix material used was an extremely soft silicone gel (Ecoflex00-30) with an elastic modulus of approximately 0.1 MPa and a spring-to-matrix modulus ratio of approximately 80:1. Sixteen silicone springs were arranged in a 4×4 rectangular array within a 40 mm square mold, with a center-to-center distance of 15 mm between adjacent springs. A small amount of uncured Ecoflex prepolymer was coated onto the bottom of the mold to fix the springs. Ecoflex components A and B were mixed in a 1:1 ratio and poured into the mold, submerging all the springs. After vacuum degassing (800 Pa, 40 min), the mixture was cured at room temperature for 24 h, and then demolded to obtain the composite material.
[0073] Step 4: Surface conductive functionalization: The composite material surface was cleaned with anhydrous ethanol. Due to the low surface energy of organosilicon, oxygen plasma treatment was performed: power 100W, pressure 40Pa, treatment time 90s. Commercial flexible conductive silver paste (DuPont5025) was uniformly coated onto the upper surface using a blade coating process, with a wet film thickness of 40μm. It was cured at 80℃ for 45min to obtain a conductive silver layer with a thickness of approximately 10μm. Conductive silver paste was dotted onto both ends of the conductive layer and copper wires were crimped together. The layer was then left to cure at room temperature for 30min.
[0074] Step 5, Packaging: A non-conductive silicone protective layer (Ecoflex00-30) with a thickness of 30 μm was coated onto the surface of the conductive layer using a spray coating process. A mask was placed at the electrode location before spray coating. The sensor was obtained after curing at room temperature for 24 hours.
[0075] The obtained flexible sensor was subjected to continuous cyclic loading-unloading tests. Test conditions: pressure 20 kPa, frequency 1 Hz, number of cycles 5000. Figure 6 The resistance change rate curve is shown as a function of the number of cycles. The peak resistance change rate during the first cycle is approximately 12%; after 1000 cycles, the peak is approximately 12.5%; and after 5000 cycles, the peak is approximately 13.5%. The sensor maintains a stable response after 5000 cycles, with a resistance change rate fluctuation of less than ±1.5%, and no substrate cracking or spring debonding occurs, indicating that the sensor has excellent fatigue resistance.
[0076] Comparative Example 1 This comparative example provides a flexible sensor without a built-in polymer directional helical spring skeleton. Its substrate material, conductive layer and packaging method are exactly the same as those in Example 1. The only difference is that it does not contain a spring structure.
[0077] The specific preparation steps are as follows: Take the same thermoplastic polyurethane granules as in Example 1, with a hardness of 60A, heat them to 200°C to melt them, and then pour them directly into a square mold with a side length of 30mm and a height of 5mm, without placing any springs. Place the mold in a vacuum drying oven, evacuate it to an absolute pressure of 1000Pa, maintain it for 30 minutes to remove air bubbles, and then cool it to room temperature to demold, obtaining a pure thermoplastic polyurethane matrix.
[0078] The same surface conductive functionalization and encapsulation steps as in Example 1 were used: oxygen plasma treatment, power 80W, pressure 30Pa, treatment time 60s; conductive carbon paste was applied by scraping, wet film thickness 50μm, and cured at 100℃ for 60min; conductive silver paste was dotted and copper wires were crimped; finally, a thermoplastic polyurethane protective layer was applied, thickness 50μm, and cured at 80℃ for 30min to obtain a springless flexible sensor.
[0079] The same test conditions as in Example 1 were used, namely, a universal testing machine combined with a resistance tester, a applied pressure of 50 kPa, and a frequency of 1 Hz. Figure 7 As shown, the peak resistance change rate during the first cycle was approximately 22%. After the 200th cycle, the peak value rose to approximately 32%, with a drift of approximately 45%. After the 500th cycle, the peak value rose to approximately 45%, with a drift of approximately 105%. After the 800th cycle, significant wrinkles and irreversible deformation appeared on the sensor surface, the peak resistance change rate had risen to approximately 60%, and the waveform was unstable. Upon further loading to approximately 1000 cycles, localized microcracks appeared in the conductive layer, and the resistance signal fluctuated violently, indicating failure. This comparative example demonstrates that the pure substrate sensor without a spring frame experiences severe performance degradation after approximately 800 to 1000 cycles, far below the stable cycle life of over 5000 cycles in Example 1.
[0080] Comparative Example 2 This comparative example provides a flexible sensor with an embedded polymer-oriented helical spring skeleton, but the spring-to-matrix modulus ratio does not meet the requirement of ≥10:1. The same spring as in Example 1, i.e., a thermosetting polyurethane spring with an elastic modulus of 250 MPa, is used, and the same spring preparation method is employed. The matrix material is changed to a thermoplastic polyurethane with a higher hardness of 90A and an elastic modulus of approximately 50 MPa. In this case, the spring-to-matrix modulus ratio is approximately 5:1, lower than the 10:1 requirement of this invention. The remaining preparation steps, including spring array layout, casting, vacuum degassing, conductive functionalization, and encapsulation, are the same as in Example 1.
[0081] The same test conditions as in Example 1 were used, namely a pressure of 50 kPa and a frequency of 1 Hz. Figure 8 As shown, the peak resistance change rate during the first cycle was approximately 18%. After 500 cycles, the peak value rose to approximately 28%, with a drift of approximately 56%. After 1000 cycles, the peak value rose to approximately 35%, with a drift of approximately 94%. After 2000 cycles, the peak value rose to approximately 48%, with a drift of approximately 167%. Upon further loading to approximately 2500 cycles, the peak resistance change rate reached approximately 55%, and localized debonding of the substrate from the spring appeared on the sensor surface. The signal fluctuation exceeded ±30%, indicating failure. This comparative example demonstrates that even with an internal spring, if the modulus ratio is below 10:1, the spring's elastic energy storage is insufficient to force the substrate to fully recover, resulting in limited durability improvement. The cycle life is far lower than the stable level maintained after 5000 cycles in Example 1.
[0082] Therefore, this invention discloses a flexible sensor with a built-in oriented helical spring skeleton and its fabrication method. It embeds a polymer oriented helical spring with an elastic modulus far exceeding that of the matrix (≥10:1) as a permanent structural skeleton within the matrix. Upon unloading, the matrix is forced to fully recover, independent of the matrix material's own resilience, resulting in a cycle life exceeding 5000 cycles. Simultaneously, it allows the use of extremely soft matrix materials, broadening the range of material choices. Unlike existing technologies that use carbon spring bodies only as conductive fillers or temporary templates for hollow structures, this invention uses the polymer spring as a structural skeleton for the first time, achieving a fundamental shift in functional positioning. The "layered rotational misalignment mold + vacuum infusion + mechanical peeling" fabrication process employed in this invention achieves low-cost, high-precision, and scalable manufacturing of polymer microsprings. This method forms a helical interconnected cavity through PMMA sheet stacking, horizontal misalignment, and layer-by-layer rotation. Vacuum infusion completely fills the cavity with polymer elastomer. After curing, easy peeling and demolding are achieved through UV adhesive dotting, avoiding the high cost and material limitations of 3D printing and micro / nano fabrication methods. Furthermore, it eliminates the need for organic solvents, making it environmentally friendly and safe. This invention achieves independent designability of sensor sensitivity and measurement range. The mechanical response is contributed by the surface conductive layer (determining sensitivity) and the spring frame (determining measurement range and linearity), respectively; their decoupled design simplifies customized development for different application scenarios. The conductive functionalization process is environmentally friendly and provides a robust bond, while the encapsulation structure further ensures long-term stability. This invention boasts advantages such as high durability, wide material adaptability, independently designable performance, and simple fabrication processes, making it promising for applications in fields such as electronic skin and intelligent prosthetics.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A flexible sensor with a built-in oriented helical spring skeleton, comprising a flexible polymer matrix, at least one polymer oriented helical spring embedded inside the flexible polymer matrix, a conductive layer disposed on the upper surface of the flexible polymer matrix, and electrodes disposed at both ends of the conductive layer, characterized in that: The elastic modulus of the polymer-oriented helical spring is higher than that of the flexible polymer matrix, and the ratio of the elastic modulus of the polymer-oriented helical spring to that of the flexible polymer matrix is... 10:1; Polymer oriented helical springs are used to bear the main stress and undergo elastic deformation under external loads, and to force the flexible polymer matrix to return to its original shape through the stored elastic potential energy after the load is unloaded.
2. A flexible sensor with a built-in directional helical spring skeleton according to claim 1, characterized in that: The polymer-oriented helical spring is made of high-modulus polymer elastomer, with an elastic modulus of 5~500MPa and a Shore hardness of 50A~80D after curing; the flexible polymer matrix is made of low-modulus polymer elastomer, with an elastic modulus of 2~20MPa and a Shore hardness of 50A~80A after curing.
3. A flexible sensor with a built-in directional helical spring skeleton according to claim 1, characterized in that: The number of polymer oriented helical springs is 1 to 100, arranged in a rectangular array, hexagonal array or ring array inside the flexible polymer matrix, with a center distance of 5 to 20 mm between adjacent springs; The conductive layer is a flexible conductive carbon paste layer with a thickness of 5~30μm, which is formed on the upper surface of the flexible polymer matrix by a scraping process. The electrodes are flexible copper wires, which are fixed to both ends of the conductive layer by conductive silver paste.
4. A flexible sensor with a built-in directional helical spring skeleton according to claim 1, characterized in that: It also includes an encapsulation layer, which covers the surface of the conductive layer and has a thickness of 20~100μm. The material is the same as that of the flexible polymer matrix.
5. A method for fabricating a flexible sensor with a built-in directional helical spring skeleton as described in any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Prepare a stacked mold with a spirally connected cavity: Take multiple thin plates and process through holes in the central area of each thin plate; stack the processed thin plates in sequence, with the center of the through holes of adjacent thin plates having a horizontal offset in the plate plane, and the adjacent thin plates rotating relative to each other around a central axis perpendicular to the plate plane at a certain angle; fix the stacked multi-layer thin plates into an integral mold, with the through holes at the top and bottom of the integral mold serving as the injection end and overflow end, respectively; Step 2, Vacuum-assisted injection molding of polymer oriented helical springs: Place the integral mold obtained in Step 1 in a vacuum environment, inject liquid high-modulus polymer elastomer precursor into the spiral cavity of the integral mold through the through hole at the injection end, and demold after solidification to obtain an independent polymer oriented helical spring. Step 3, Combining the spring with the flexible matrix: Place at least one polymer oriented helical spring obtained in Step 2 into a matrix mold; pour uncured low-modulus polymer elastomer precursor into the matrix mold to completely submerge the polymer oriented helical spring; after curing, demold to obtain a flexible matrix composite material with a polymer oriented helical spring skeleton embedded inside. Step 4, Surface conductive functionalization: A conductive layer is formed on the upper surface of the composite material obtained in step 3, and electrodes are formed at both ends of the conductive layer; Among them, the elastic modulus of the polymer-oriented helical spring is higher than that of the flexible polymer matrix, and the ratio of the elastic modulus of the polymer-oriented helical spring to that of the flexible polymer matrix is ≥10:
1.
6. The preparation method according to claim 5, characterized in that: In step 1, the thin plate is a polymethyl methacrylate thin plate, and the quantity is 10 to 50 pieces; the through hole is an elliptical through hole with a major axis of 1.0 to 3.0 mm and a minor axis of 0.5 to 1.5 mm; the horizontal offset of the center of the elliptical through hole of two adjacent thin plates in the plate plane is 0.1 to 1.0 mm, and the two adjacent thin plates are rotated relative to each other about a central axis perpendicular to the plate surface by 15° to 45°; the adjacent thin plates are bonded and fixed together by UV curing adhesive.
7. The preparation method according to claim 6, characterized in that: In step 2, the absolute pressure of the vacuum environment is 100~1000Pa; the injection adopts a vacuum-assisted injection method, injecting the liquid high-modulus polymer elastomer precursor from the through hole at the injection end until liquid flows out from the through hole at the overflow end, then stop the vacuuming and keep the vacuum standing for 5~15 minutes; demolding adopts a mechanical peeling method to peel off all the thin plates layer by layer. The high-modulus polymer elastomer is a thermosetting polyurethane, silicone rubber, or polyurea elastomer. The elastic modulus after curing is 5~500MPa. The curing conditions are: thermosetting polyurethane is cured at 80~120℃ for 1~4h, and silicone rubber is cured at room temperature for 24h or at 80℃ for 1h.
8. The preparation method according to claim 7, characterized in that: In step 3, the number of polymer oriented helical springs is 1 to 100, which are placed in an array in the matrix mold, with the center distance between adjacent springs being 5 to 20 mm; Before placing the spring, first coat the bottom of the base mold with an uncured low-modulus polymer elastomer precursor, and then gently press the spring to fix it. After casting, place the mold in a vacuum environment and maintain it under an absolute pressure of 500~1500Pa for 20~60 minutes to remove air bubbles, and then cure it according to the curing conditions of the base material. The low-modulus polymer elastomer is thermoplastic polyurethane, silicone rubber or thermosetting polyurethane, with an elastic modulus of 2~20MPa after curing. The curing conditions are as follows: thermoplastic polyurethane is cooled and shaped, silicone rubber is cured at room temperature to 80℃ for 1~24h, and thermosetting polyurethane is cured at 80~120℃ for 1~4h.
9. The preparation method according to claim 8, characterized in that: Step 4 involves setting the conductive layer by: wiping the surface of the composite material obtained in step 3 clean with anhydrous ethanol; treating its upper surface with oxygen plasma under the following conditions: power 50-100W, pressure 20-50Pa, and time 30-120s; uniformly coating the surface with conductive paste using a scraping process, resulting in a wet film thickness of 30-80μm; curing at 80-120℃ for 30-90min to obtain a conductive layer with a thickness of 5-30μm; applying conductive silver paste to both ends of the conductive layer and pressing it with flexible copper wires, then curing at room temperature for 30-60min.
10. The preparation method according to claim 9, characterized in that, The process also includes step 5, encapsulation: coating a non-conductive flexible protective layer with a thickness of 20~100μm onto the surface of the conductive layer where the electrodes have been led out. The material of the flexible protective layer is the same as that of the low-modulus polymer elastomer. Before coating, a mask or pre-reserved opening is set at the electrode lead-out position, and encapsulation is completed after curing.
Citation Information
Patent Citations
Elastic sensing body and preparation method of elastic complex in elastic sensing body
CN107287685A
Elastic transplanting method, preparation method and application of spiral structure material
CN116330688A
Stretchable pressure-sensitive material as well as preparation method and application thereof
CN116376310A